Late Graft Loss After Kidney Transplantation: Is "Death With Function" Really Death With a Functioning Allograft?. Issue 7 (July 2020) - Gaston, Robert S.; Fieberg, Ann; Helgeson, Erika S.; Eversull, Jason; Hunsicker, Lawrence; Kasiske, Bertram L.; Leduc, Robert; Rush, David; Matas, Arthur J.
Abstract : Background: About half of late kidney allograft losses are attributed to death with function (DWF), a poorly characterized outcome. An ongoing question is whether DWF is a consequence of chronic allograft dysfunction. Using the prospective Long-term Deterioration of Kidney Allograft Function study database, we sought to better define the impact, phenotype, and clinical course of DWF in the current era. Methods: Three thousand five hundred eighty-seven kidney recipients with functional grafts at 90 days post-transplant were followed prospectively for a median of 5.2 years. Results: Characteristics at transplantation in those with DWF (N = 350, 9.8%) differed from those who otherwise lost their grafts (death-censored graft failure [DC-GF], N = 295, 8.2%) or maintained function (N = 2942, 82.0%); DWF patients were older, sicker, and had been on dialysis longer, with more preexisting cardiovascular disease, whereas DC-GF patients experienced more early rejection, more acute rejection after 90 days, and a clinically significant decrease in kidney function before graft failure. In contrast, the clinical course after transplantation in DWF patients did not differ before death from those who maintained function throughout. Conclusions: DWF and DC-GF in kidney transplant recipients represent differing clinical phenotypes occurring in distinct patient populations. Reducing the impact of DWF requires better definition of causes and clinical course and then trials of therapies to improve outcomes. Composite endpoints in clinical trials that group DWF and DC-GF together may obscure important clinical findings. Abstract : Supplemental Digital Content is available in the text.